Traditional Chinese Medicine Prolongs Progression-Free Survival and Enhances Therapeutic Effects in Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor (EGFR-TKI)Treated Non-Small-Cell Lung Cancer (NSCLC) Patients Harboring EGFR Mutations - Tang, Mo (Med Sci Monit, 2019)
BACKGROUND: Lung cancer is the most common cause of cancer-associated deaths worldwide. This study aimed to investigate the efficacy and safety of Traditional Chinese Medicine combining EGFR-TKIs in treatment of NSCLC patients harboring EGFR mutations. MATERIAL/METHODS: This study involved 153 advanced-stage NSCLC patients harboring EGFR mutations. Patients were divided into a Control group (administered EGFR-TKI, n=61) and an Experimental group (administered Traditional Chinese Medicine combining EGFR and TKI, n=92). Progression-free survival (PFS) was evaluated for exon 19 deletion and/or 21 deletion patients. Disease control rate (DCR) was assessed to observe therapeutic effects. Adverse effects, including rashes, diarrhea, ALT/AST increase, dental ulcers, and onychia lateralis, were also evaluated. RESULTS: TCM combining EGFR-TKI (90.11%) demonstrated no DCR improvement compared to single EGFR-TKI (83.33%) (p>0.05). Median PFS (mPFS) of TCM combining EGFR-TKI (13 months) was significantly longer compared to that in the single EGFR-TKI group (8.8 months) (p=0.001). For 19DEL mutant NSCLC, the mPFS (11 months) in TCM combining EGFR-TKI was significantly longer compared to single EGFR-TKI (8.5 months) (p=0.007). The mPFS of L858 mutant NSCLC patients in EGFR-TKI combining CTM (14 months) was significantly longer compared to single EGFR-TKI (9.5 months) (p=0.015). TCM combining EGFR-TKI was more inclined to prolong mPFS of NSCLC with exon 21 deletion. TCM combining EGFR-TKI illustrated no additional adverse effects in NSCLC patients (p=0.956). CONCLUSIONS: Application of Traditional Chinese Medicine prolonged progression-free survival and enhanced therapeutic effect in NSCLC patients harboring EGFR mutations receiving EGFR-TKI treatment. Meanwhile, adjunctive Chinese medicine combining EGFR-TKI in NSCLC with EGFR mutations caused no adverse effects.